2021
DOI: 10.1080/17450128.2021.1975858
|View full text |Cite
|
Sign up to set email alerts
|

Sexual debut and risk behaviors among orphaned and vulnerable children in Zambia: which protective deficits shape HIV risk?

Abstract: Orphaned and vulnerable children (OVC) are not only affected by, but also rendered at-risk of, HIV due to overlapping deficits in protective assets, from school to household financial security. Drawing from a protective deficit framework, this study examines correlates of sexual risk -including multiple sexual partnerships, unprotected sex, and age at sexual debut -among OVC aged 13-17 years in Zambia. In May-October 2016, a two-stage stratified random sampling design was used to recruit OVC and their adult ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
2
2
1
Order By: Relevance
“…A majority of sexual behaviors of sexually experienced non-institutionalized orphans were either coercive encounters, exploitation, or forced or transactional sex ( 25 27 ). This finding is at variance with what was reported in the Zambian study among orphans and vulnerable children (OVC), where early sexual debut was reported among out-of-school orphans who also engaged in income-generating activities, a separate study of adolescent orphans also found that female double orphans are more likely to experience an early sexual debut than non-orphans ( 22 , 27 ).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…A majority of sexual behaviors of sexually experienced non-institutionalized orphans were either coercive encounters, exploitation, or forced or transactional sex ( 25 27 ). This finding is at variance with what was reported in the Zambian study among orphans and vulnerable children (OVC), where early sexual debut was reported among out-of-school orphans who also engaged in income-generating activities, a separate study of adolescent orphans also found that female double orphans are more likely to experience an early sexual debut than non-orphans ( 22 , 27 ).…”
Section: Discussioncontrasting
confidence: 93%
“…This sociodemographic study is similar to that of a study on underserved adolescent orphans in Sagamu, Ogun State, where a majority of respondents were females and were at least 15 years of age, but it is at variance with a Zambian study that reported an even distribution of age and sex among samples ( 21 , 22 ).…”
Section: Discussionsupporting
confidence: 81%
“…HIV prevalence was signi cantly higher among orphaned youth who did not use a condom at last sex. This data supports existing evidence of heightened infection rate and high sexual risk behaviour among youth who are orphans [32,33]. This is contrary to suggestions that maternal transmission is a more likely explanation, than sexual transmission for heightened HIV infection among orphans [25].…”
Section: Discussionsupporting
confidence: 80%
“…Socio-behavioral factors included the following: ever had sexual intercourse (no, yes); age of sexual debut (had sex before the age of 15 years, had sex at age15 years and older); age of sexual partner (partner more than 5 years younger, partner within 5 years of age, partner more than 5 years older); number of sexual partners in the last 12 months (one partner, two or more partners); condom use at last sex (yes, no); alcohol use using the Alcohol Abuse Disorder Identification Test (AUDIT) score [abstainers, low risk (with scores in the range of 1-7), risky/hazardous level (8)(9)(10)(11)(12)(13)(14)(15), high risk/harmful (16)(17)(18)(19), very high risk (20+)]. HIVrelated factors included the following: correct knowledge and rejection of all myths about HIV transmission (yes, no); selfperceived risk of HIV infection (yes, no); ever tested for HIV (yes, no); awareness of HIV status (yes, no); and the survey laboratory results determined an HIV status (HIV positive, HIV negative).…”
Section: Methodsmentioning
confidence: 99%
“…Risky sexual behaviors increase susceptibility to sexually transmitted infections, including HIV, and unplanned or unwanted pregnancies, which in turn can lead to deleterious health, social, and economic consequences (8)(9)(10). The vulnerability of orphans to sexual risk behaviors have been attributed to socio-demographic (such as being younger, gender disparities, low educational attainment, and poverty) and sociobehavioral factors (such as substance use, peer influence, sexual predation, and lack of family support) (8,11). These culminate in high-risk abortion, psychological disorders, teenage pregnancy, school dropout, and early marriage (2).…”
Section: Introductionmentioning
confidence: 99%